Uspołecznienie a prywatyzacja zadań publicznych w świetle rozwoju społeczeństwa obywatelskiego - Szymkow, Bartosz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article is to show the differences between the general point of privatization and socialization of public issues done by public administration. In the article I try to show up the differences between nomenclatural meaning of privatisation, seen as a buisness site and socialisation, seen more as a civil action of people living in society (III sector) and acting pro publico bono. It is also to show how important it is in the general reception of society, what finnaly effects better understanding and building up of civil society.
Keywords: civil society; privatization; third sector; socialization